Nuclear Import and Export in Plants and Animals - Tzfira, Tzvi.; Citovsky, Vitaly; SpringerLink (Online service) (Boston, MA : Springer US, 2005)
Nuclear Import and Export in Plants and Animals provides insight into the remarkable mechanisms of nuclear import and export. This book covers a range of topics from the nuclear pore structure, to nuclear import and export of macromolecules in plant and animal cells. In addition, the book covers the special cases of nuclear import of Agrobacterium T-DNA during plant genetic transformation, nuclear import and export of animal viruses, and nuclear intake of foreign DNA. A chapter on research methods to study nuclear transport concludes the book.
Structure of the Nuclear Pore -- Integral Proteins of the Nuclear Pore Membrane -- Subnuclear Trafficking and the Nuclear Matrix -- Nuclear Import and Export Signals -- Nuclear Import of Plant Proteins -- Nuclear Import of Agrobacterium T-DNA -- Regulation of Nuclear Import and Export of Proteins in Plants and Its Role in Light Signal Transduction -- Nuclear Export -- Nuclear Protein Import -- The Molecular Mechanisms of mRNA Export -- Nuclear Import and Export of Mammalian Viruses -- Nuclear Import of DNA -- Research Methodologies for the Investigation of Cell Nucleus.
Keywords: Life sciences; Cell biology; Life Sciences; Cell Biology; Electronic books